A diabolical voice : heresy and the reception of the Latin Mirror of simple souls in late medieval Europe - Trombley, Justine L., 1987- (Medieval societies, religions, and cultures., 2023)
"This book examines the Latin manuscript tradition of the condemned mystical treatise The Mirror of Simple Souls, written by Marguerite Porete (d. 1310). It shows how the Latin Mirror was the target of multiple condemnations and refutations in the fourteenth and fifteenth centuries"--